2020
DOI: 10.1186/s12936-020-03185-w
|View full text |Cite
|
Sign up to set email alerts
|

District-level approach for tailoring and targeting interventions: a new path for malaria control and elimination

Abstract: Despite huge investments and implementation of effective interventions for malaria, progress has stalled, with transmission being increasingly localized among difficult-to-reach populations and outdoor-biting vectors. Targeting difficult pockets of transmission will require the development of tailored and targeted approaches suited to local context, drawing from insights close to the frontlines. Districts are best placed to develop tailored, locally appropriate approaches. We propose a reorganization of how ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…By giving nets away to friends and family, communities may be compensating for inadequate campaign planning. National malaria programs may consider including local leadership and shift toward a more decentralized approach to improve the design of LLIN campaign distributions (Gosling et al, 2020). Third, we were able to show that in areas with limited resources to carry out the WHO cone bioassay, the measurement of insecticide content by bromine x-ray uorescence might be an accurate alternative methodology to estimate the bio-e cacy of LLINs.…”
Section: Discussionmentioning
confidence: 81%
“…By giving nets away to friends and family, communities may be compensating for inadequate campaign planning. National malaria programs may consider including local leadership and shift toward a more decentralized approach to improve the design of LLIN campaign distributions (Gosling et al, 2020). Third, we were able to show that in areas with limited resources to carry out the WHO cone bioassay, the measurement of insecticide content by bromine x-ray uorescence might be an accurate alternative methodology to estimate the bio-e cacy of LLINs.…”
Section: Discussionmentioning
confidence: 81%
“…By giving nets away to friends and family, communities may be compensating for inadequate campaign planning. National malaria programmes may consider including local leadership and shift toward a more decentralized approach to improve the design of LLIN campaign distributions [ 34 ]. Third, it has been shown that in areas with limited resources to carry out the WHO cone bioassay, the measurement of insecticide content by bromine x-ray fluorescence might be an accurate alternative methodology to estimate the bio-efficacy of LLINs.…”
Section: Discussionmentioning
confidence: 99%
“…By giving nets away to friends and family, communities may be compensating for inadequate campaign planning. National malaria programs may consider including local leadership and shift toward a more decentralized approach to improve the design of LLIN campaign distributions (Gosling et al, 2020). Third, we were able to show that in areas with limited resources to carry out the WHO cone bioassay, the measurement of insecticide content by bromine x-ray fluorescence might be an accurate alternative methodology to estimate the bio-efficacy of LLINs.…”
Section: Discussionmentioning
confidence: 99%